Hepatitis C virus: Current steps toward elimination in Germany and barriers to reaching the 2030 goal. Issue 2 (4th June 2021) - Sarrazin, Christoph; Boesecke, Christoph; Golsabahi‐Broclawski, Solmaz; Moog, Gero; Negro, Francesco; Silaidos, Carmina; Patel, Polly; Lohmann, Kristina; Spinner, Christoph D.; Walcher, Stephan; Wedemeyer, Heiner; Wörns, Marcus‐Alexander
Abstract: Hepatitis C virus (HCV) affects over 70 million people globally, with an estimated 399 000 HCV‐related deaths in 2016. The World Health Organization (WHO) has set a goal to eliminate HCV by 2030. Despite the availability of direct‐acting antivirals—highly effective and well‐tolerated therapies for HCV—many patients infected with HCV in Germany have not initiated treatment, including a majority of those who are aware of their positive diagnosis. Barriers to screening, diagnosis, and treatment are major factors taking many countries off track for HCV elimination by 2030. Identifying country‐specific barriers and challenges, particularly in at‐risk populations such as people who inject drugs or men who have sex with men, has the potential to create tailored programs and strategies to increase access to screening or treatment and engage at‐risk populations. This review aims to report the current steps toward HCV elimination in Germany, the country‐specific barriers and challenges that will potentially prevent reaching the 2030 HCV elimination goal and describe good practice examples to overcome these barriers.